Kant’s Enlightenment - Fleischacker, Sam (Con-Textos Kantianos. International Journal of Philosophy, 2015)
I urge here that Kant’s essay “What is Enlightenment?” be read in the context of debates at the time over the public critique of religion, and together with elements of his other writings, especially a short piece on orientation in thinking that he wrote two years later. After laying out the main themes of the essay in some detail, I argue that, read in context, Kant’s call to “think for ourselves” is not meant to rule out a legitimate role for relying on the testimony of others, that it is directed instead against a kind of blind religious faith, in which one either refuses to question one’s clerical authorities or relies on a mystical intuition that cannot be assessed by reason. Both of these ways of abandoning reason can be fended off if we always submit our private thoughts to the test of public scrutiny: which is why enlightenment, for Kant, requires both free thinking, by each individual for him or herself, and a realm of free public expression in which individuals can discuss the results of their thinking.